Une renaissance. Doctrines, littérature et pensée juridique du xvie siècle en France - Géraldine Cazals (Clio@Themis)
The history of Sixteenth century French legal thought has, in recent years, known significant developments, and even, shall we say, a true renaissance, since the works devoted by French historians of law to that period have grown considerably. When looking at these works, we can notice that the study of doctrines have been flourishing, through the analysis of the contributions of some authors and actors of the period. Furthermore, we can observe a growing consideration for the contexts and the materiality of the texts, within the framework of multidisciplinary approaches. This contributes to the development of a critical history of the French Sixteenth century legal thought, which allows the analysis of law within a wider cultural space, and allows the French history of law to break up with both disciplinary and nationalist isolation.